2014
DOI: 10.1002/cne.23518
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory and multisynaptic spines, and hemispherical synaptic specialization in the posterodorsal medial amygdala of male and female rats

Abstract: The density of dendritic spines is sexually dimorphic and variable throughout the female estrous cycle in the rat posterodorsal medial amygdala (MePD), a relevant area for the modulation of reproductive behavior in rats. The local synaptic activity differs between hemispheres in prepubertal animals. Here, we used serial section transmission electron microscopy to produce three-dimensional reconstructions of dendritic shafts and spines to characterize synaptic contacts on MePD neurons of both hemispheres in adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 90 publications
1
47
0
Order By: Relevance
“…Then, from the 3D reconstructed images, spines were classified and counted according to morphological criteria based on spine length (SL), neck length (NL), neck diameter (ND), head diameter (HD) and the number of protrusions from a single stalk (Dall'Oglio, Dutra, Moreira, & Rasia‐Filho, ; Zancan et al., and references therein). Based on their shapes, spines were classified into the following: (a) thin (when SL > HD and HD > ND), (b) mushroom‐like (HD ≫ ND), (c) stubby/wide (HD > SL), (d) ramified (with a single stalk that branches in two heads) or (e) atypical (when showing a transitional aspect between classes or an unusual shape not classified in the other classes (based on Arellano, Benavides‐Piccione, DeFelipe, & Yuste, ; Brusco et al., , ; Dall'Oglio et al., ; Harris et al., ; Stewart, Popov, Kraev, Medvedev, & Davies, ; Zancan et al., and references therein). Representative examples are shown in Figures and .…”
Section: Methodsmentioning
confidence: 99%
“…Then, from the 3D reconstructed images, spines were classified and counted according to morphological criteria based on spine length (SL), neck length (NL), neck diameter (ND), head diameter (HD) and the number of protrusions from a single stalk (Dall'Oglio, Dutra, Moreira, & Rasia‐Filho, ; Zancan et al., and references therein). Based on their shapes, spines were classified into the following: (a) thin (when SL > HD and HD > ND), (b) mushroom‐like (HD ≫ ND), (c) stubby/wide (HD > SL), (d) ramified (with a single stalk that branches in two heads) or (e) atypical (when showing a transitional aspect between classes or an unusual shape not classified in the other classes (based on Arellano, Benavides‐Piccione, DeFelipe, & Yuste, ; Brusco et al., , ; Dall'Oglio et al., ; Harris et al., ; Stewart, Popov, Kraev, Medvedev, & Davies, ; Zancan et al., and references therein). Representative examples are shown in Figures and .…”
Section: Methodsmentioning
confidence: 99%
“…We also looked for the presence and shape of spinules (smaller protrusions usually extending from the head of a spine; Brusco et al. ; Stewart et al. ) and filopodium (a thin and elongated protrusion with no apparent head; García‐López et al.…”
Section: Methodsmentioning
confidence: 99%
“…It was not possible to obtain 150–300 ultra‐thin serial sections to perform 3D reconstructions of TEM images from our samples as obtained for rats or mice (see Fiala & Harris, ; Brusco et al. ; Stewart et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al used immunolabeling against glial fibrillary acidic protein (GFAP) and green fluorescent protein for fluorescence immunohistochemical detection and assayed GFAPimmunoreactivity (GFAP-ir) in adult male MC4R-GFP transgenic mice [9]. They reported that GFAP-ir cells were mainly labeled in the medial subdivision of the central amygdala (CeM) and sparsely distributed in the lateral subdivision of the central amygdala (CeL) and basolateral amygdala (BLA) [9], suggesting that the CeM is a major subdivision in the amygdala which participates in the regulation of astrocytic activity [11][12][13]. This observation was in line with previous evidence indicating a possible local restructuring of astrocytic cytoskeleton in the medial amygdala after myocardial infarction/heart failure in rats [14].…”
Section: Amygdala and Sudden Unexpected Death In Epilepsymentioning
confidence: 98%